2008
DOI: 10.1177/1553350608315954
|View full text |Cite
|
Sign up to set email alerts
|

A High-Definition Exoscope System for Neurosurgery and Other Microsurgical Disciplines: Preliminary Report

Abstract: An 8-mm diameter rigid lens telescope with a focal distance of 20 cm was developed for open microsurgery. The telescope was attached to a 3-chip high-definition digital camera and then to a high-definition monitor. A pneumatic scope holder permitted repositioning. The optical quality of the device was compared with the operating microscope with a step wedge and 1-mm grid paper. Craniotomies and microsurgical dissections with the telescope system (high-definition exoscope system) were performed in a live pig mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 7 publications
1
74
0
2
Order By: Relevance
“…The most striking finding of the study was the consensus of all participants of the superb HD image quality and clear resolution of anatomic detail, which has been reported in previous studies in neurosurgery, otolaryngology, and gynecology. 9,[12][13][14] The VITOM imaging system lends itself well to neonatal and pediatric surgical cases by providing clear visualization of the operation to all operating room personnel, many of whom would typically not be able to see the small operative field because of limitations of space, lack of magnifying loupes, or both.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking finding of the study was the consensus of all participants of the superb HD image quality and clear resolution of anatomic detail, which has been reported in previous studies in neurosurgery, otolaryngology, and gynecology. 9,[12][13][14] The VITOM imaging system lends itself well to neonatal and pediatric surgical cases by providing clear visualization of the operation to all operating room personnel, many of whom would typically not be able to see the small operative field because of limitations of space, lack of magnifying loupes, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in which the manual-holder exoscope was used have mentioned that the lack of binocular stereopsis is a significant limitation for approaching deep-seated cranial lesions, which is in part due to the limitations of the scope holder that require continuous repetitive manual movement to create a coaxial direct line-of-site, resulting in optimal visualization. 22,23 However, we found that the dynamic movement of the robotic arm within the surgical corridor, in both its axial and in particular the rotational planes, provided an important means to compensate for the inherent lack of binocular stereoscopic vision through motion and parallax. This is in keeping with the previous experience that we have described, suggesting that dynamic movement represents a critical compensation for 2D image generated by neuroendoscopic surgery.…”
Section: Rovot-m Technical Feasibility and Cranial Applicationsmentioning
confidence: 81%
“…In particular, Mamelak et al have described a high-definition exoscopic payload for use in cranial and spinal neurosurgery. 22,23 However, this particular exoscope is attached to a static holder that requires repeated manual repositioning to achieve each new viewing angle and is not specifically designed based on the performance of the other 4 components of the optical chain. The ROVOT-m, on the other hand, comprises an exoscopic (telescopic) payload that is coupled to an automated robotic arm, which dynamically repositions it through a global positioning navigation system using a computer-machine interface that creates a fully integrated system, wherein each component is designed to enhance the overall performance of the collective elements of the optical chain.…”
Section: Rovot-m Technical Feasibility and Cranial Applicationsmentioning
confidence: 99%
“…It has already been attempted to find alternative visualization methods. 8,19 CONCLUSION From an optical point of view, current operating microscopes seem to meet the requirements of neurosurgery in most aspects. However, ergonomically speaking, further developments are highly desirable.…”
Section: Discussionmentioning
confidence: 98%
“…7 The costs of the high-end technology are size and unhandiness of these devices. 8 The dimensions of the optical components and the necessity of their strict geometrical alignment are opposed to the manufacturers' endeavor of improving ergonomic aspects. The surgeon often has to operate under, ergonomically speaking, unfavorable, and hindering conditions, especially when the patient is positioned semisitting and the surgeon has to encompass the voluminous microscope while performing fine dissection in deep-seated locations.…”
mentioning
confidence: 98%